GRAMMATICAL ERROR IN WRITING DESCRIPTIVE TEXT AT SEVENTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL IN CIMAHI - Kasini Kasini; Miftah Pusparaini (IKIP Siliwangi, 2019)
The purpose of this research is to find the type of grammatical error in students’ writing descriptive text made by the seventh graders of junior high school in Cimahi.The population consists of five classes, and we took 20 students to be sample. The study found out that the types of grammatical error are: Omission, Addition,Misformation and Misordering. The total of each type of error are: Omission 39.34%, Misordering 28.68%, Addition 18.03%, and Misformation 13.93%. Based on the research, it can be assumed that students usually miss to put a word like to be must appear in a well-formed sentence. And the lowest frequently of error is misformation, it is because in descriptive text there are rarely use plural words.